The implementation of new carriage technologies in the Lithuanian railway transport and establishment of the prospective markets for railway and road transport - Butkevičius, Jonas (Transport, 2003)
This article provides the analysis of the possibilities to instal new technologies in the Lithuanian railways the building of a high speed railway line I in Kreta corridor. It is advisable to project this line as a mixed one, i.e. intended for both passenger and goods traffic. The research carried out by the author has shown that light transport dominates in passenger transportation among four cities of Lithuania Vilnius, Kaunas, Klaipeda and Siauliai, which transports even 81,3% of direct passengers. Buses carry 14,9% and only 3,8% of passengers are carried by railway transport. Therefore the main problem public transport is facing is to“get the passengers back” from light transport means, i.e. cars. The prospective railway and road transport markets in local, intercity and international passengers' transportations are also established in this work.First Published Online: 19 Dec 2011